The Influence of Social Media on Young People's Self-Esteem - Vicol, Florina Madalina (New Trends in Psychology, 2024)
Since the beginning of the 21st century, our world has experienced a strong acceleration of digitization. Worldwide, 25% of people use platforms like Facebook, Twitter, TikTok and Instagram, etc. Social media is revolutionizing the way we interact and connect with each other. Research has shown that both the behavioral and neurological responses to social media abuse are similar to those caused by drug, alcohol or gambling addiction. Among the negative effects of excessive use of social networks are aggression, social isolation, loneliness, obesity, sleep disorders and deterioration of relationships with others. Among other things, dopamine is responsible for the sensation experienced when we perform a desirable action, such as eating sweets. Considering the above, it is necessary to take measures to mitigate the negative effects of screen abuse, especially in children and adolescents, in order to restore a psychological normality and create a solid foundation for their harmonious development. So, it is important to emphasize that social networks are not per se harmful, but it all depends on how and to what extent we use them.